Current Practices for Estimating Special Texts: Linguistic and Terminographic Expertizing - Татьяна Петрова [Tat’jana Petrova] (Jezikoslovni zapiski, 2020)
This article analyzes modern practices of estimating special texts: linguistic expertizing and terminology dictionary reviewing. It is shown that the objects of linguistic expertizing and reviewing are special texts. Linguistic expertizing and terminographic expertizing are equivalent but not identical estimating practices, although they share some common features.